(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
While reading this article, you will learn about the methodology of preparation for PIRLS tasks through bibliotherapy and the direct support of bibliotherapy in self-healing and the use of bibliotherapy in overcoming social and emotional difficulties that may arise in elementary school students. considered